Pengaruh Penggunaan Media Slide Powerpoint terhadap Minat Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti Kelas XI di SMKN 3 Kota Solok - Dian Nova Dinda; Supriadi Supriadi; Afrinaldi Afrinaldi; Ulva Rahmi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Advances in information and communication technology have had a significant impact on the world of education, especially in improving the effectiveness and efficiency of the learning process. One technology that is often used is Microsoft PowerPoint as learning media. This study aims to analyze the effect of using PowerPoint media on student learning interest in Islamic Religious Education and Ethics subjects at SMKN 3 Solok City. This research uses a quantitative approach with a quasi-experimental method using a nonequivalent control group design. Data were collected through tests, questionnaires, and observations, and analyzed using normality, homogeneity, and t-test. The results showed that the use of PowerPoint media had a positive and significant effect on students' interest in learning. The experimental group that used PowerPoint had a higher level of interest in learning than the control group. This is due to the presentation of material that is more interactive, interesting, and systematic, so as to motivate students to be actively involved in the learning process. The t-test value shows that there is a significant difference between the experimental and control groups, with a t-count value of 5.384 (p < 0.05). This study concludes that PowerPoint learning media is effective in increasing students' interest in learning Islamic Religious Education and Ethics subjects. Hopefully, this finding can be a reference for educators in developing technology-based learning models that are more innovative and relevant to modern learning needs.